Top Management Support, Green Intellectual Capital and Green HRM: A Proposed Framework for Sustainability - ALKAF, Abdur Rachman; YUSLIZA, Mohd Yusoff; EHIDO, Amauche Justina; SAPUTRA, Jumadil; MUHAMMAD, Zikri (Journal of Environmental Management and Tourism, 2023)
Sustainability has become a crucial aspect of organisational strategy, with many organisations implementing sustainable actions to mitigate environmental effects and reinforce social responsibility. However, sustainability adoption in organisations may be challenging due to some factors including the lack of resources, conflicting priorities, and resistance to change. Considering that sustainability is a long-term agenda that requires continuous commitment and investment in human resources, companies should understand the drivers of their sustainability adoption to develop strategies that foster company longevity. This study discussed the resource-based view (RBV) theory that emphasises the strategic resources that could be utilised by an organisation to gain sustainable competitive advantage. A framework was proposed to demonstrate the ability of leveraging organisational key resources such as top management support (TMS), green intellectual capital (IC), and Green Human Resource Management (HRM) in promoting the adoption of sustainable practices in organisations. This research has contributed to the sustainability literature by establishing a unified framework that could be applied to assess the impacts of TMS, GIC, and Green HRM on sustainability and determine the ability of Green HRM to strengthen the relationships between TMS, GIC, and sustainability through mediation. The study results would assist the top management and policymakers in understanding the importance of their support towards sustainable development. The results would also enhance the understanding of the importance of continuous investment in green knowledge creation among employees to reap the benefits from GIC and Green HRM practices. Finally, researchers could adopt the proposed framework in future studies for further empirical explorations of the drivers of sustainability.